Hubungan Tingkat Stres dan Asupan Zat Gizi Makro dengan Status Gizi pada Mahasiswa Tingkat Akhir Jurusan Gizi Kemenkes Poltekkes Kupang Tahun 2025 - mersi loemnanu; Asmulyati S Saleh; Maria Goreti Pantaleon (Poltekkes Kemenkes Kupang, 2026)
The final year of college is a transitional period prone to high stress, which theoretically can affect eating behavior and macronutrient intake, thereby impacting nutritional status. Nutrition students are expected to have better self-control; however, the pressure of final projects remains a risk factor for psychological well-being and dietary management. This study aims to analyze the relationship between stress levels and macronutrient intake (protein, fat, carbohydrates) with nutritional status among final-year students in the Department of Nutrition at the Kupang Ministry of Health Polytechnic in 2025. This is an analytical observational study with a cross-sectional design. The study was conducted in May–June 2025 at the Department of Nutrition, Kupang Public Health Polytechnic. The sample consisted of 100 final-year students selected using purposive sampling. Data were statistically analyzed using the Chi-Square test. The majority of respondents experienced very severe stress (89.0%). Most respondents had an inadequate intake of macronutrients, including protein (70.0%), fat (93.0%), and carbohydrates (92.0%). The distribution of nutritional status based on BMI showed the following categories: severely underweight (18.0%), underweight (19.0%), overweight (12.0%), and obese (1.0%). Statistical test results showed no significant association between stress levels (p=0.111), protein intake (p=0.396), fat intake (p=0.582), and carbohydrate intake (p=0.616) and nutritional status. Conclusion: There was no significant association between stress levels and macronutrient intake and nutritional status among senior college students. High stress levels and low macronutrient intake did not directly reflect the nutritional status of the respondents in this study, which was likely influenced by other factors such as the duration of stress or physical activity.